Discussões matemáticas de jovens e adultos em um ambiente de aprendizagem de modelagem matemática - Ludmila Iara Andrade Silva (2018)
In this research I investigated the mathematical discussions that occurred among students of Educação de Jovens e Adultos - EJA (Youth and Adult Education) in a Mathematical Modeling environment. The Mathematical discussions refer to the mathematical concepts and ideas or procedures belonging to the mathematical discipline. I carried out a qualitative research through unstructured observations and participants, so that the data were collected in a Junior High School Class of the Projeto de Ensino Médio de Jovens e Adultos PROEMJA (Project of High School for Youth and Adults). The PROEMJA is linked to the Programa de Educação Básica de Jovens e Adultos (Basic Education Program for Youth and Adults) of the Federal University of Minas Gerais (UFMG), which is located at the Pedagogical Center of UFMG, in the city of Belo Horizonte. Observations were recorded through audio, video, questionnaire and field diary recordings. From the analysis of the data it was possible to infer that the production of the mathematical discussions comes from the relation that the students of the EJA establish between the Mathematics and their personal trajectory, life experience. In other words, mathematical discussions were produced with the convergence of synergies between the school and non-school experiences of individuals with mathematics. In addition, the results of this study have also indicated that the occurrence of the mathematical discussions of the EJA students can offer us theoretical subsidies on the characteristics of these discussions in a Mathematical Modeling Environment.